Pluralizing RRI pedagogy: ‘cachando’ tactical lessons towards critical resistance for responsible research and innovation learning - Martín Perez Comisso; Ben Gansky; Lindsay A. Smith (Journal of Responsible Innovation)
Opening up RRI to values and ways of knowing and doing beyond its European and Anglophone origins has become a focal area for scholars and practitioners. This article addresses the role of RRI pedagogy within the broader scope of this transformation, an under-examined topic in the literature. Drawing on the theoretical framework of critical resistance, we explore how RRI pedagogy might offer engaged scholars and educators opportunities to ‘risk themselves’ by intentionally destabilizing their authority as knowers. We offer a case study of a multinational, multilingual, multi-institutional learning initiative drawing from decolonial thinking to resist Anglophone epistemic hegemony in responsible research education. Our case study points to tactics for unsettling pedagogical habits by working across language differences, centering learners’ contexts, attending to the labor of teaching itself, and ‘searching for decoloniality’.